2013
DOI: 10.1371/journal.pone.0076760
|View full text |Cite
|
Sign up to set email alerts
|

Can Environment Predict Cryptic Diversity? The Case of Niphargus Inhabiting Western Carpathian Groundwater

Abstract: In the last decade, several studies have shown that subterranean aquatic habitats harbor cryptic species with restricted geographic ranges, frequently occurring as isolated populations. Previous studies on aquatic subterranean species have implied that habitat heterogeneity can promote speciation and that speciation events can be predicted from species’ distributions. We tested the prediction that species distributed across different drainage systems and karst sectors comprise sets of distinct species. Amphipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…Third, the discovery of cryptic diversity is critical to understanding anthropogenic biotic changes, invasions and ecosystem health [7]. Thus, cryptic diversity is a vital component of biological diversity [8,9], and its discovery is central to documenting fundamental units in ecology [10], evolution and conservation [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the discovery of cryptic diversity is critical to understanding anthropogenic biotic changes, invasions and ecosystem health [7]. Thus, cryptic diversity is a vital component of biological diversity [8,9], and its discovery is central to documenting fundamental units in ecology [10], evolution and conservation [2].…”
Section: Introductionmentioning
confidence: 99%
“…WorldClim). Cryptic diversity may be predictable from analysis of environmental data [8], and comparative phylogeographic research has demonstrated broadly congruent patterns of cryptic diversity in multiple species occupying the same fragmented biome [22 -24]. In such conditions, cryptic divergence may be driven by random processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…n. is geographically far from its sister species N. sohrevardensis. This is a surprise, as Niphargus species are in general poorly vagile, and closely related species often share the same geographic region (Fišer et al 2008, Trontelj et al 2009, Meleg et al 2013. The distance between the two species is 323.5 km.…”
Section: Discussionmentioning
confidence: 99%
“…5 (Tamura et al 2011) and Patristic distances from a maximum likelihood (ML) tree as described in Fourment and Gibbs (2006) in the PATRIS-TIC v1.0 program. Patristic distances have been broadly used in Niphargus taxonomy so far; as such warrant compatibility of the results across different studies (Léfebure et al 2006, Meleg et al 2013. Diagnosis -The rami in uropod I have equal length.…”
Section: Phylogenetic Analyses and Molecular Divergencementioning
confidence: 99%
“…Firstly, phylogenetic analyses suggest that morphological differentiation does not follow phylogenetic relationships. Closely related species may be morphologically either very different (Fišer et al, 2008;Trontelj et al, 2012), or morphologically indistinguishable from each other (e.g., Trontelj et al, 2009;Meleg et al, 2013). Molecular analyses revealed also the second important characteristic of Niphargus, i.e., that small distributional ranges are rather rule than exception (Trontelj et al, 2009).…”
Section: Introductionmentioning
confidence: 99%